Answer
1
Work Step by Step
We use the Properties of Exponents, step by step...
P0. $a^{0}=1,\ a^{1}=a$
P1. $a^{m}\cdot a^{n}=a^{m+n}$
P2. $\displaystyle \frac{a^{m}}{a^{n}}=a^{m-n}$ , $ \displaystyle \frac{1}{a^{n}}=a^{-n}$
P3. $(a^{m})^{n}=a^{mn}$
P4. $(ab)^{m}=a^{m} b^{m}$
P5. $(\displaystyle \frac{a}{b})^{m}=\frac{a^{m}}{b^{m}}$
P6. Rational exponents: $a^{m/n}=(a^{1/n})^{m}\sqrt[n]{a^{m}}$
-----------------------------
$\displaystyle \frac{y^{10}\cdot y^{-4}}{y^{6}}$= ... P1...
$=\displaystyle \frac{y^{10+(-4)}}{y^{6}}=\frac{y^{6}}{y^{6}}$= ...P2...
$=y^{6-6}=y^{0}$= ...P$0$...
$=1$